Sustainability Indicator: An Initial Parameter for Convenience Product - Bulan Prabawani; Sudharto Prawata Hadi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
The environmental awareness of consumer has been growing along with the increase of knowledge, education and access to information. The demand from the government, media, and community has also increasingly escalated the pressure to companies to produce environmentally friendly products. This eventually encourages greenwashing practices extensively which are unfavorable to consumers because the practice is frequently included as marketing scam. In addition, the existing environmentally-based certification is primarily oriented to the planet and profit aspects of the triple bottom lines and tends to ignore the community. Hence, this study reviews a variety of green-based certifications or sustainability indicators which has existed particularly in Indonesia and their potential for the development of convenience products, products which are consumed in high frequency since they are cheap and consumed daily. This research involves explorative analysis using open secondary data from public journalism, media releases, academic references, and official webpages. Furthermore, this research describes current green-based certifications and presents the initial concept of a sustainability indicator which involved the planet and humans concurrently as well as adopt Proper label as product labelling.